(untitled) (Development Service Industry Management, 2025)
The article examines the current state of the competitive landscape of retail chains in Ukraine, which is marked by fierce competition and adaptation to transformations caused by war and economic uncertainty. To conduct the analysis, a theoretical definition of market concentration and retailers focusing on improving the offer of goods, service and interaction with customers, despite the difficulties of staff shortages and logistics problems, is formulated. The evolution of the NNI index as an indicator of market conditions and competition in an environment where new technologies and differentiation play a key role, attracting international companies and stimulating the development of e-commerce, is considered. The challenges facing the competitive market are identified, in particular the economic crisis and rising prices, which require retail companies to be flexible and adaptable. The dynamics of online sales are analyzed, which form a complex and changing competitive environment, and retail chains are implementing digital solutions and improving the quality of service to remain relevant. In conclusion, it is proposed to improve the strategies of retail chains in response to changes in consumer preferences and the growth of online shopping; to attract global experience in the new realities of digitalization; to adapt to macroeconomic challenges and implement digital innovations, omnichannel solutions and environmental practices. Retail chains are adapting to the conditions of a changing competitive environment that emphasizes the phenomena of omnichannel, sustainable development, digital innovations in technologies. Consumers expect a seamless shopping experience in both physical and digital channels, which requires retailers to integrate trading platforms. In the context of economic stratification and the growth of conscious consumption, companies are reviewing pricing strategies and assortment, implementing environmental practices and technologies, such as artificial intelligence and blockchain, to increase efficiency and sustainability.